Los hombres son todos iguales - Shimura Rodríguez, Kinshiro Raúl (2025)
Men are all the same is a project sparked by Carlo Collodi’s The Adventures of Pinocchio. It gathers intuitive questions that aim to tear open the complexity around body, power, and desire, and to reconstruct it uncomfortably in tension with the contemporary context in which this artistic practice, made of representation, research, and lies, takes place. It stands on three elements: (1) an installation of three sculptures that give corporeality to Pinocchio and Geppetto, (2) a series of large format drawings that operate as writing and sustain an expressive thread without depending on verbal language, and (3) a text structured on the original tale’s table of contents, with voices of Geppetto, Pinocchio, Pepe Grillo, and other guests, in dialogue with theoretical reflections presented as narratives and morals that lie, intersect, and contradict to complicate the other components. Written language operates as a constructive, suggestive, and amplifying device, just as ambiguous as it is drastic, that sections, caresses, and penetrates the body of work, but not as a definitive explanation. It accompanies the process of murdering meaning and leaving it in suspense. The guiding hypothesis holds that the discursive complement tends to draw attention away from the corporeal component, while incompleteness is assumed as a tactic and frustration as the material driver of the process. The inevitable conclusion is that men are all the same.